Creating a GIS Database for Pre-Contact Archaeological Sites in the Red Cedar River Valley. - McDonald, Jacob M. (My University, 2009)
The Red Cedar River is located in western Wisconsin, flowing southward from its headwaters in Sawyer County through Washburn, Barron, and Dunn Counties until joining the Chippewa River near Dunnville. For the past 125 years, considerable archaeological research has been conducted along the Red Cedar River and its tributaries. The purpose of this project was to create a geographic information system (GIS) database in order to consolidate this archaeological data into a uniform format.
Color poster with text and maps describing research conducted by Jacob McDonald, advised by Robert J. Barth.
Keywords: Red Cedar River Valley (Wis.)--Antiquites; Archaeology--Wisconsin--Red Cedar River Valley; Archaeology--Wisconsin--Databases; Posters